(untitled) (The Pakistan Development Review, 2002)
To eliminate the subsidy on the canal irrigation system, the Government of Pakistan has decided to reform the management, intending to make it more efficient, equitable, transparent, and able to take care of the sustainability of the world’s largest contiguous irrigation network. The water users are being entrusted with greater role in the management through the formation of Farmers’ Organisations (FOs) to operate and maintain secondary canals and pay for full cost of water delivery. Ultimate payer will be the farmer. The economic viability of the reforms, therefore, much depends on farmers’ ability and willingness to pay for the cost of irrigation water delivery, which is expected to rise. This paper estimates financial liabilities of the farmers in the post-reform scenario, and assesses their capacity and willingness to pay for liabilities in the provinces of Punjab and Sindh. One distributary in each of the two provinces is studied as the reference distributary, where FOs have already been formed. The cost of desired level of operation and maintenance levels are worked out using secondary data for 1997-98. With these costs, the water users in the Punjab and Sindh provinces need to pay Rs 333 and Rs 373 per ha for their water service, respectively. The estimated O&M costs form about 5.4 and 3 percent of production costs and 3.8 and 3.5 percent of the net income in the Punjab and Sindh provinces respectively. The farmers’ net income from crop enterprise is higher than the cost of water. Thus, an average farmer has the potential to pay for water. Recent experience of Hakra 4-R Distributary FO suggests that the farmers are also willing to pay for water service, if they are organised properly.